Application of risk analysis within value management: a case study in dam engineering - Rohaninejad, Mohsen; Bagherpour, Morteza (Journal of Civil Engineering and Management, 2013)
Nowadays, considering uncertainties and complexities in dam engineering problems, implementation of risk analysis is essential more than before. On the other hand, reliability analysis is an efficient approach which can be applied in order to quantify the identified risks. By applying such analyses, a designer can therefore define and develop different scenarios in order to evaluate the effect of identified risks. The risk management process can be further implemented within a value management cycle where the potential alternatives should be evaluated and finally the best-known alternative must be selected. In order to measure the efficiency of risk analysis approach in a dam, a case study is studied and then implemented. The result of the reliability analysis for the piping phase shows a conservative approach with a low risk during the dam design process. Based on the value analysis, two different scenarios are then developed. In the first scenario, the piping phase is considered as a high risk issue; and in the second scenario, the risk is considered as its minimum acceptable threshold. Based on the obtained results, this can be summarized: utilizing risk analysis for improvement of the decision-making process can be efficiently defined and developed as a fundamental strategy in water resource projects.